Membrane fouling behavior and control strategies during ultrafiltration of polymer-flooding produced water - Mengyang He; Jun Xu; Jiahou Hao; Lai Lyu; Hongyuan Fang; Jing Lu; Dongsheng Zhao; Wenyu Zheng; Gengmin Jiang; Shuili Yu; Linna Wang (Journal of Environmental Chemical Engineering, 2026)

Enhanced biodegradation of sulfaquinoxaline by functional bacteria: Identifying the rate-limiting step, metabolite toxicity, and dissemination risks of antibiotic resistance genes - Linna Zhang; Yuxia Zhao; Sufang Wang; Xin Fan; Aijuan Zhou; Bowei Zhao; Yu Yang; Xiuping Yue; Yanjuan Gao (Journal of Environmental Chemical Engineering, 2026)

Co-exposure of sequential extreme weather and non-biodegradable/biodegradable microplastics (NBMPs/BMPs) on soil bacterial communities and the extracellular polymeric substances (EPS)-extracellular enzyme interaction mechanisms - Xinyu Yang; Yulian Ma; Xin Wang; Yue Sun; Qianzhi Zeng; Yunhong Pu; Bowen Yang; Yaxuan Wu; Xinran Su; Linna Shi; Shuang Li; Wenzhuo Sui; et al. (Journal of Environmental Chemical Engineering, 2026)

Inhibiting Ru over-oxidation in RuO2 via vanadium doping for efficient oxygen evolution reaction toward acid and alkaline water electrolysis - Wenzhuo Zhang; Linna Wang; Xiang Li; Yunling Ji; Guisheng Xu; Yikang Cao; Shufen Wang; Jian Li (Fuel, 2026)

Phenothiazine-based self-assembled monolayer enabling high-efficiency and scalable inverted perovskite solar cells - Huilin Xie; Mingxin Wang; Xiaofeng He; Peng Wang; Miaoxin Li; Cheng Zhong; Qunliang Song; Yong Hua; Fei Wu; Linna Zhu (Chemical Engineering Journal, 2026)

Sulfobutylether-(hydroxypropyl-β-cyclodextrin) bonded silica as stationary phase for enhancing chiral separation in liquid chromatography - Linna Xu; Ankang Li; Jialong Wang; Gaosheng Yang; Liqin Lin; Keer Yu; Huizhen Ni; Wentao Xu; Junchao Zhu; Dongping Cheng; Shengqiang Tong (Analytica Chimica Acta, 2026)

DOM-mediated interaction of DOM-enzyme-pollutants affected the toxicity of combined aged tire wear particles (aged-TWPs) and polyfluoroalkyl substances (PFASs) in soil under successive extreme weather stress - Xin Wang; Yulian Ma; Xinyu Yang; Yue Sun; Wenzhuo Sui; Yunhong Pu; Qianzhi Zeng; Yaxuan Wu; Bowen Yang; Xinran Su; Shuang Li; Linna Shi; et al. (Journal of Environmental Management, 2026)

Effects of Perfluoroheptanoic Acid (PFHpA) on Bacterial Community, Elemental Cycling and ARGs Transmission in Sediment - Shengnan Shi; Xinran Su; Linna Shi; Shuang Li; Yunhong Pu; Qianzhi Zeng; Bowen Yang; Yaxuan Wu; Yue Sun; Yulian Ma; Xinyu Yang; Xin Wang; et al. (Water, Air, & Soil Pollution, 2026)

Contrasting effects of partial organic substitution and its inoculation with phosphate-solubilizing bacteria on stoichiometric imbalances and phosphorus fractions accumulation after six-year application in a rice paddy - Xinxin You; Wenyi Xu; Linna Du; Sheng Wang; Yan Zhou; Xiaomin Ma; Hua Qin; Junhui Chen (Soil and Tillage Research, 2026)

Enhancing the whipping properties of blend whipped cream using coconut diglyceride through crystallization modulation and interfacial stabilization - Huijie Dong; Chonghao Wang; Fengyan Wang; Linna You; Yan Chen; Shangde Sun (Food Chemistry, 2026)

Explainable machine learning-assisted near-infrared spectroscopy for rapid detection of adulterants in sweet potato starch - Mengmeng Li; Linna Guo; Mengyu Zhang; Yujie Wang (Food Control, 2026)

Niaodukang for the treatment of chronic kidney disease: Regulation of the TRAF3/NF-κB2 signaling pathway and its improvement of the intestinal barrier - Juan Xu; Lei Wang; Hong Wang; Jie Pang; Linna Liu; Ting Zhang; Ling Yuan; Xiaoxue Cui; Qian Jiang; Yanlin Li (Tissue and Cell, 2026)

Divergent biodegradation responses to single and combined antibiotic exposure in a simultaneous denitrification and methanogenesis system: Impacts on microbial community structure, metabolite dynamics, and resistome - Fang Yang; Linna Zhang; Sufang Wang; Jierong Zheng; Aijuan Zhou; Yu Yang; Xiuping Yue; Bowei Zhao; Yanjuan Gao (Journal of Environmental Chemical Engineering, 2026)

Multiscale investigation of oxidative aging on thiol–functionalized montmorillonite: Correlating structural and chemical degradation to the reduced affinity for Hg(II) and MeHg - Ning Wang; Penggang Pei; Ge Gao; Yundi Kan; Linna Zhou; Bozhen Yu; Yuebing Sun (Journal of Environmental Chemical Engineering, 2026)

Chitosan-modified photocrosslinked silk fibroin hydrogels loaded with RA-loaded self-assembled bilayer nanoparticles promote healing of infected wounds - Zheng Sun; Linna Wang; Ye Peng; Dixin Xing; Yining Wang; Sufang Zhang; Chaofan Ji; Xinping Lin; Fengming Dong; Ningbo Qin (Chemical Engineering Journal, 2026)

Interactions of microbiota during solid-state cereal vinegar fermentation - Dantong Liu; Zhenhua Su; Qi Han; Liting Wang; Linna Tu; Yongjian Yu; Menglei Xia; Yanbing Shen; Yu Zheng; Min Wang (Trends in Food Science & Technology, 2026)

Insights into low temperature adaptation in Epinephelus awoara through integrated genome and transcriptome analysis - Linna Wang; Shuai Chen; Zhentong Li; Yang Liu; Shihao Wang; Tangtang Ding; Fengfan Yang; Chunbai Zhang; Linlin Li; Wensheng Li; Qingbin Wang; Xia Zhao; et al. (Aquaculture, 2026)

Freeze–thaw cycling effects on Pb and Cd immobilization by green waste compost in contaminated soil - Jie Ma; Chenchen Wang; Linna Suo; Yuanxin Liu; Xiangyang Sun (Journal of Soils and Sediments, 2026)

Genome-wide identification of NF-Y family in Carya illinoinensis and CiNF-YC6 role in fatty acid biosynthesis - Linna Wang; Lina Zou; Zixian Yao; Jinhua He; Shunran Zhang; Yan Xiang (Plant Cell Reports, 2026)

Steady-state modeling and analysis of solid–liquid two-phase flow in vertical and flexible pipelines for deep-sea mining - Yumiao Wang; Ri Zhang; Linna Chen; Yong Liu; Liwei Yu (Ocean Engineering, 2025)

Olive oil additive enhances hyphal growth and triterpenes accumulation in submerged fermentation of Grifola frondosa - Qiaoyu Wang; Chenmeng Wan; Ke'er Xiao; Zijian Tong; Ziteng Zhao; Xinyu Meng; Mukaddas Sai; Yajie Bao; Lili Guan; Hongxia Ma; Linna Du (Fungal Biology, 2025)

Antioxidant and antimicrobial activities of octenyl succinic anhydride modified Tamarind/Portulaca polysaccharide coating incorporated with protocatechuic acid methyl ester and its application in cherry tomatoes preservation - Miaole Zhang; Hong Chen; Linna Wang; Shaoying Zhang; Youwei Yu (Food Packaging and Shelf Life, 2025)

Characterization of intestinal microbiota in patients with psoriasis combined with metabolic syndrome - Yiyue Yuan; Linna Zhao; Haining Ding; Yinshuang Hua; Hongmei Wang; Manlin Zhao (Molecular and Cellular Biochemistry, 2025)

The role of circSUCLG2 in mediating inflammatory response and bone remodeling imbalance in diabetic osteoporosis - RenZhou Wang; LinNa Ma (Molecular & Cellular Toxicology, 2025)

Bromine (Br)-modified magnetic Zr metal organic framework for highly efficient adsorption and detection of sugar phosphates in biological samples - Linna Han; Zixu Wang; Wanfang Feng; Qing Xia; Yucun Niu; Liyan Liu (Analytica Chimica Acta, 2025)

Identification of the bHLH transcription factor family and functional characterization of CibHLH141 and CibHLH127 in response to iron deficiency stress of pecan (Carya illinoinensis) - Lina Zou; Linna Wang; Jinhua He; Zixian Yao; Shunran Zhang; Yan Xiang (Plant Science, 2025)

Exploring the effects of food by-product HMF on pepsin structure, function, and physiological activity from a binding perspective - Shuyuan Zhang; Zimeng He; Linna Gao; Ziye Zhou; Yiming Wang; Xiting Li; Yongye Zheng; Baozhu Chi; Xun Tuo (Food Research International, 2025)

Embryonic and Larval Development of an Interspecific Grouper Backcross Between the Kelp Grouper (Epinephelus moara) ♀ and KGGG (E. moara ♀ × E. lanceolatus ♂) ♂ - Yidan Xu; Yongsheng Tian; Shihao Wang; Tangtang Ding; Linna Wang; Zhentong Li; Linlin Li; Yang Liu (Fishes, 2025)
Backcrossing serves as an effective tool for interspecific gene introgression, facilitating germplasm improvement. To develop superior grouper aquaculture varieties, in this study, a backcrossed breed was constructed by crossing a male hybrid grouper, KGGG (Epinephelus moara ♀ × E. lanceolatus ♂), with a female parent kelp grouper (KG; E. moara). Here, we observed embryonic, larval development, and morphological changes in KG × KGGG. Additionally, the total length and body weight of the backcrossed breed and maternal parent were compared at 160 d post hatching (dph). The results showed that fertilization and the hatching rate were 73.23 ± 4.23% and 51.74 ± 3.67%, respectively, and the egg size was 0.89 ± 0.03 mm. Hatching occurred 23:19 h after fertilization at 25 ± 1 °C, and the newly hatched larvae were 1.94 ± 0.13 mm in length. Furthermore, at 160 dph, the total length and body weight of the backcrossed breed were 1.2-fold and 1.9-fold greater, respectively, when compared with those of the maternal parent. Importantly, it is possible that backcrossed KG × KGGG could become a dominant strain in grouper aquaculture practices.

Synergistic bioaugmentation: Serratia sp. WKD and carboxymethyl cellulose-modified nano-zero-valent iron enhance malachite green decolorization by activated sludge - Linna Du; Xinjiao Dong; Huan Wu; Gang Li; Jiacheng Zhou; Yiqing Wu; Yanping Xiao; Jing Qin; Xiu Wang (Journal of Water Process Engineering, 2025)

Antioxidant and antibacterial activities of chitosan/pullulan sustained-release coatings loaded with carvacrol microcapsules, and their application in fresh-cut green bell pepper preservation - Linna Wang; Hesheng Wang; Limin Guo; Qiyuan Feng; Miaole Zhang; Youwei Yu; Shaoying Zhang (Food Packaging and Shelf Life, 2025)

Titanium dioxide nanoparticles disturb glucose homeostasis in association with impaired enteroendocrine cell differentiation - Kai Zou; Linna Du; Jing Qin; Jiacheng Zhou; Yanping Xiao; Xixi Song; Hongxia Liu; Xiu Wang (Food and Chemical Toxicology, 2025)

The pass-through mechanism for carbon emission cost under ETS with different accounting principles: a focus on construction supply chains - Shanshan Huang; Bing Wang; Linna Geng; Jiajun Ma (Environment, Development and Sustainability, 2025)

Pregnancy-induced changes in the toll-like receptor pathway in the ovine duodenum - Linna Gao; Haiquan Ding; Qianqian Shi; Xinxin Wang; Leying Zhang; Ling Yang (Veterinary Immunology and Immunopathology, 2025)

Identification of phenols and their formation network during the brewing process of Shanxi aged vinegar - Jing Liu; Jiao Wang; Boya Zhu; Kai Liang; Yushi Zhang; Jia Song; Linna Tu; Yu Zheng; Min Wang (Food Chemistry, 2025)

Dilute formic acid and alkaline oxidation relay treatment for the whole-fraction efficient gradient separation of space Arundo donax - Wenlong Xu; Xuanjie Zou; Ruotong Cui; Dameng Wang; Qilin Guo; Yanchao Shang; Jialin Zhao; Peijie Zong; Yifan Wu; Haozhe Zhang; Biao Liang; Linna Deng; et al. (Journal of Cleaner Production, 2025)

Dynamic simulation of core power control for SPWR based on dynamic model bank - Zheng Li; Xiaoyu Li; Linna Wang; Wenjie Zeng (Annals of Nuclear Energy, 2025)

β-Cyclodextrin based magnetic hyper-crosslinked polymer: A recyclable adsorbent for effective preconcentration of triazine herbicides in complex sample matrices - Linna Guo; Qianqian Wang; Qiuhua Wu; Chun Wang; Baojiang Chen (Food Chemistry, 2025)

A light-responsive multifunctional composite hydrogel for synergistically photodynamic/photothermal enhanced chemodynamic and electrical stimulation therapy of wound infection - Shiyu Wang; Xueshan Zhao; Linna Zhang; Kang Dai; Zhenyu Zhang; Haibo Wang; Jun Gu (Chemical Engineering Journal, 2025)

Corrigendum to ‘Heavy metals and metalloids exposure and liver function in Chinese adults - A nationally representative cross-sectional study’ [Environ. Res. 252-P2 (2024) 118653] - Shiyu Wang; Yuebin Lyu; Saisai Ji; Nankun Liu; Bing Wu; Feng Zhao; Zheng Li; Yingli Qu; Yuanduo Zhu; Linna Xie; Yawei Li; Zheng Zhang; et al. (Environmental Research, 2024)

Effects of harvest times on the production and quality of Bletilla striata - Jie Wang; Aimin Lv; Linna Yao; Man Zhang; Hailing Fang; Juanping Jiang; Jianjun Zhu; Ying Zheng (Acta Physiologiae Plantarum, 2024)

Examining the impact of mineral export controls on sustainable energy transition in the global south - Linna Han; Xihui Haviour Chen; Yong Wang; Yen Hai Hoang (Resources Policy, 2024)

Impact of corticosteroid doses on prognosis of severe and critical COVID-19 patients with Omicron variant infection: a propensity score matching study - Shiyao Wang; Ziying Chen; Xinran Zhang; Xiaojing Wu; Yuqiong Wang; Qi Zhang; Linna Huang; Xiaoyang Cui; Ying Cai; Xu Huang; Jingen Xia; Sichao Gu; et al. (Inflammopharmacology, 2024)
Background There is lack of research on corticosteroid use for severe and critical COVID-19 patients with Omicron variant infection. Methods This multi-center retrospective cohort study involved 1167 patients from 59 ICUs across the mainland of China diagnosed with severe or critical SARS-CoV-2 Omicron variant infection between November 1, 2022, and February 11, 2023. Patients were segregated into two groups based on their corticosteroid treatment—usual dose (equivalent prednisone dose 30–50 mg/day) and higher dose (equivalent prednisone dose > 50 mg/day). The primary outcome was 28-day ICU mortality. Propensity score matching was used to compare outcomes between cohorts. Results After propensity score matching, 520 patients in the usual dose corticosteroid group and 260 patients in the higher dose corticosteroid group were included in the analysis, respectively. The mortality was significantly higher in the higher dose corticosteroid group (67.3%, 175/260) compared to the usual dose group (56.0%, 291/520). Logistic regression showed that higher doses of corticosteroids were significantly associated with increased mortality at 28-day (OR = 1.62,95% CI 1.19–2.21, p = 0.002) and mortality in ICU stay (OR = 1.66,95% CI 1.21–2.28, p = 0.002). Different types of corticosteroids did not affect the effect. Conclusions The study suggests that higher-dose corticosteroids may lead to a poorer prognosis for severe and critical COVID-19 patients with Omicron variant infection in the ICU. Further research is needed to determine the appropriate corticosteroid dosage for these patients.

The potential impact of 6PPD and its oxidation product 6PPD-quinone on human health: A case study on their interaction with human serum albumin - Chaolan Chen; Linna Gao; Pei Ding; Shuyuan Zhang; Xiaowei Wang; Kaiyu Yang; Yikun Zhou; Baozhu Chi; Xun Tuo (Chemosphere, 2024)

Bionic nanopore recognition receptors for single-molecule enantioselectivity studies of chiral drugs - Rikun Cui; Zhenzhao Wang; Linna Li; Lili Liu; Zhen Li; Xingtong Liu; Tingting Chen; Ayesha Rauf; Xiaofeng Kang; Yanli Guo (Analytica Chimica Acta, 2024)

Dietary seafood as a potential modifier in the relationship between per- and polyfluoroalkyl substances (PFASs) burden and prediabetes/diabetes: Insights from a nationally representative cross-sectional study - Yingli Qu; Nan Sheng; Saisai Ji; Zheng Li; Jinghua Wang; Yitao Pan; Xiaojian Hu; Xulin Zheng; Yawei Li; Haocan Song; Linna Xie; Wenli Zhang; et al. (Journal of Hazardous Materials, 2024)

Heavy metals and metalloids exposure and liver function in Chinese adults — A nationally representative cross-sectional study - Shiyu Wang; Yuebin Lyu; Saisai Ji; Nankun Liu; Bing Wu; Feng Zhao; Zheng Li; Yingli Qu; Yuanduo Zhu; Linna Xie; Yawei Li; Zheng Zhang; et al. (Environmental Research, 2024)

Paleontology Knowledge Graph for Data-Driven Discovery - Yiying Deng; Sicun Song; Junxuan Fan; Mao Luo; Le Yao; Shaochun Dong; Yukun Shi; Linna Zhang; Yue Wang; Haipeng Xu; Huiqing Xu; Yingying Zhao; et al. (Journal of Earth Science, 2024)

Exploring efficient reductive dechlorination in nitrate-containing groundwater: Does sulfidated microscale zero-valent iron coupled with anaerobic bacteria increase sustainability? - Litao Wang; Linna Jia; Jia Xin; Lijun Chen; Weiran Meng; Jiahui Lu (Chemical Engineering Journal, 2024)

Modulation of the RAC1/MAPK/ERK signalling pathway by farnesyl diphosphate synthase regulates granulosa cells proliferation in polycystic ovary syndrome - Xiaoli Guo; Yijuan Cao; Qing He; Linna Chen; Qing Wang; Jingbo Zhang; Wenqiang Lv; Bei Zhang; Xueyan Zhou (Human Cell, 2024)

MgO-modified biochar by modifying hydroxyl and amino groups for selective phosphate removal: Insight into phosphate selectivity adsorption mechanism through experimental and theoretical - Xiaoyu Zhang; Youpeng Xiong; Xiaohao Wang; Zhennan Wen; Xiaolin Xu; Jianbing Cui; Zhongwang Liu; Linna Wei; Xiongfang An (Science of The Total Environment, 2024)

CiAP2/ERF65 and CiAP2/ERF106, a pair of homologous genes in pecan (Carya illinoensis), regulate plant responses during submergence in transgenic Arabidopsis thaliana - Hongxia Liu; Yangang Lan; Linna Wang; Nianqin Jiang; Xiaoyue Zhang; Min Wu; Yan Xiang (Journal of Plant Physiology, 2024)

Comparative transcriptome analysis of hybrid Jinhu grouper (Epinephelus fuscoguttatus ♀ × Epinephelus tukula ♂) and Epinephelus fuscoguttatus under temperature stress - Pengfei Duan; Yongsheng Tian; Zhentong Li; Shuai Chen; Linlin Li; Xinyi Wang; Linna Wang; Yang Liu; Jieming Zhai; Wensheng Li; Qingbin Wang; Wenhui Ma; et al. (Aquaculture, 2024)

Synthesis and application of wetland plant-based functional materials for aqueous antibiotics removal - Tao Fu; Linna Du; Suqing Wu; Min Zhao; Xiangyong Zheng; Zhiquan Wang; Yejian Zhang; Chunzhen Fan; Wen Wang; Fuyuan Ran; Ping Lin; Chunjie Zhong (Science of The Total Environment, 2024)

Challenges to environmental governance arising from the Russo–Ukrainian conflict: Evidence from carbon emissions - Linna Han; Zixuan Zhou; Baofeng Shi; Yong Wang (Journal of Environmental Management, 2024)

Genome-wide identification of the Carya illinoinensis bZIP transcription factor and the potential function of S1-bZIPs in abiotic stresses - Nianqin Jiang; Linna Wang; Yangang Lan; Hongxia Liu; Xiaoyue Zhang; Wei He; Min Wu; Hanwei Yan; Yan Xiang (Tree Genetics & Genomes, 2023)

Mutant p53R211* ameliorates inflammatory arthritis in AIA rats via inhibition of TBK1-IRF3 innate immune response - Yaling Zeng; Jerome P. L. Ng; Linna Wang; Xiongfei Xu; Betty Yuen Kwan Law; Guobing Chen; Hang Hong Lo; Lijun Yang; Jiujie Yang; Lei Zhang; Liqun Qu; Xiaoyun Yun; et al. (Inflammation Research, 2023)
Background Rheumatoid arthritis (RA) is an autoimmune inflammation disease characterized by imbalance of immune homeostasis. p53 mutants are commonly described as the guardian of cancer cells by conferring them drug-resistance and immune evasion. Importantly, p53 mutations have also been identified in RA patients, and this prompts the investigation of its role in RA pathogenesis. Methods The cytotoxicity of disease-modifying anti-rheumatic drugs (DMARDs) against p53 wild-type (WT)/mutant -transfected RA fibroblast-like synoviocytes (RAFLSs) was evaluated by MTT assay. Adeno-associated virus (AAV) was employed to establish p53 WT/R211* adjuvant-induced arthritis (AIA) rat model. The arthritic condition of rats was assessed by various parameters such as micro-CT analysis. Knee joint samples were isolated for total RNA sequencing analysis. The expressions of cytokines and immune-related genes were examined by qPCR, ELISA assay and immunofluorescence. The mechanistic pathway was determined by immunoprecipitation and Western blotting in vitro and in vivo. Results Among p53 mutants, p53 R213* exhibited remarkable DMARD-resistance in RAFLSs. However, AAV-induced p53 R211* overexpression ameliorated inflammatory arthritis in AIA rats without Methotrexate (MTX)-resistance, and our results discovered the immunomodulatory effect of p53 R211* via suppression of T-cell activation and T helper 17 cell (Th17) infiltration in rat joint, and finally downregulated expressions of pro-inflammatory cytokines. Total RNA sequencing analysis identified the correlation of p53 R211* with immune-related pathways. Further mechanistic studies revealed that p53 R213*/R211* instead of wild-type p53 interacted with TANK-binding kinase 1 (TBK1) and suppressed the innate immune TBK1–Interferon regulatory factor 3 (IRF3)–Stimulator of interferon genes (STING) cascade. Conclusions This study unravels the role of p53 R213* mutant in RA pathogenesis, and identifies TBK1 as a potential anti-inflammatory target.

Preparation of hypercrosslinked porous polymer with manifold functional groups for sensitive determination of phenylurea herbicides in beverages and celtuce samples - Linna Guo; Miao Tian; Zhi Li; Qianqian Wang; Qiuhua Wu; Lin Hao; Chun Wang (Food Chemistry, 2023)

Evaluation of Encequidar as An Intestinal P-gp and BCRP Specific Inhibitor to Assess the Role of Intestinal P-gp and BCRP in Drug-Drug Interactions - Jessica Chu; Erika Panfen; Linna Wang; Anthony Marino; Xue-Qing Chen; R. Marcus Fancher; Raviraj Landage; Omprakash Patil; Salil Dileep Desai; Devang Shah; Yongjun Xue; Michael Sinz; et al. (Pharmaceutical Research, 2023)

Copper/gold-modified porphyrinic metal–organic frameworks nanoprobes for enhanced photodynamic/chemodynamic therapy - Jiahe Zhang; Linna Chang; Ran Hao; Gangwan Zhang; Tao Liu; Zekai Li; Tianyou Wang; Leyong Zeng (Chemical Engineering Journal, 2023)

Effect of sunflower seed husk and rape straw in total mixed ration during peri-puberty on testis development in Hu lambs - Xiuxiu Weng; Wanhong Li; Hui Xu; Shirong Li; Xinji Wang; Kaidong Li; Linna Xu; Jiamei Liu; Xiangpeng Yue; Fadi Li (Small Ruminant Research, 2023)

Understanding the interactions of NaClO oxidant with coal for intensified hydraulic fracturing effectiveness - Jiang Liu; Yili Kang; Qiang Chen; Liangliang Jiang; Jingyi Wang; Ian Gates; Lijun You; Linna Sun; Dawei Liu; Jin Sun (Gas Science and Engineering, 2023)

Effect of non-permeable cryoprotectant sucrose on the development of spotted knifejaw (Oplegnathus punctatus) embryos - Linlin Li; Yongsheng Tian; Zhentong Li; Pengfei Duan; Xinyi Wang; Shuai Chen; Linna Wang; Yang Liu; Qingbin Wang; Wensheng Li; Xia Zhao; Wenhui Ma; et al. (Cryobiology, 2023)

Biotic and abiotic drivers of ecosystem multifunctionality: Evidence from the semi-arid grasslands of northern China - Congwen Wang; Wanying Yu; Linna Ma; Xuehua Ye; Enkhmaa Erdenebileg; Renzhong Wang; Zhenying Huang; Tuvshintogtokh Indree; Guofang Liu (Science of The Total Environment, 2023)

Catalytic probes based on aggregation-induced emission-active Au nanoclusters for visualizing MicroRNA in living cells and in vivo - Wenhao Shu; Xuetao Zhang; Hongmei Tang; Linna Wang; Manxiao Cheng; Jingwen Xu; Rong Li; Xiang Ran (Analytica Chimica Acta, 2023)

Quantitative paleogeographical reconstructions and basin evolution of South China during the Ordovician - Linna Zhang; Junxuan Fan; Bo Wang; Yuandong Zhang; Jianbo Liu; Hao Huang; Qing Chen (Earth-Science Reviews, 2023)

Assessing nickel sector index volatility based on quantile regression for Garch and Egarch models: Evidence from the Chinese stock market 2018–2022 - Linna Lu; Yalin Lei; Yang Yang; Haoqi Zheng; Wen Wang; Yan Meng; Chunhong Meng; Liqiang Zha (Resources Policy, 2023)

Identification of a phosphotriesterase-like lactonase in Klebsiella sp. and enhancement of its biofouling mitigation potential by γ-caprolactone - Xinjiao Dong; Dong Liu; Linna Du; Shimei Ge; Yizhu Zhao; Yaru Li; Chuanhua Wang (International Biodeterioration & Biodegradation, 2023)

Efficient degradation and decolorization of triphenylmethane dyes by Serratia sp. WKD under extreme environmental conditions and the mechanism - Linna Du; Huan Wu; Gang Li; Yi Wei; Fei Wang; Ligen Xu; Xinjiao Dong (International Biodeterioration & Biodegradation, 2023)

One-step synthesis of aqueous CdTe/CdSe composite QDs toward efficiency enhancement of solar cell - Daxue Du; Linna Wang; Dong Ding; Yikai Guo; Jiayao Xu; Feiyang Qiao; Haiyan Wang; Wenzhong Shen (Chemical Engineering Journal, 2023)

Quantification of the antagonistic and synergistic effects of Pb2+, Cu2+, and Zn2+ bioaccumulation by living Bacillus subtilis biomass using XGBoost and SHAP - Sheng Wang; Ying Zhou; Xinxin You; Bing Wang; Linna Du (Journal of Hazardous Materials, 2023)

Evaluating the human use efficiency of urban built environment and their coordinated development in a spatially refined manner - Yi Bao; Zhou Huang; Linna Li; Han Wang; Jiayuan Lin; Gang Liu (Resources, Conservation and Recycling, 2023)

Heterosis in growth and low temperature tolerance in Jinhu grouper (Epinephelus fuscoguttatus ♀ × Epinephelus tukula ♂) - Shuai Chen; Yongsheng Tian; Zhentong Li; Yang Liu; Ziqi Li; Pengfei Duan; Linlin Li; Xinyi Wang; Linna Wang; Xinlei He; Xia Zhao; Wensheng Li; et al. (Aquaculture, 2023)

Research status on remediation of eutrophic water by submerged macrophytes: A review - Dongsheng Wang; Xinyu Gan; Zhiquan Wang; Shunfeng Jiang; Xiangyong Zheng; Min Zhao; Yonghua Zhang; Chunzhen Fan; Suqing Wu; Linna Du (Process Safety and Environmental Protection, 2023)

The effect of underwater supplemental light on the growth of V.spinulosa Yan and the restoration process of water - Jinshan Zhao; Pu Yang; Yuye Lin; Xiaoyao Zhu; Jiaxin Wang; Xinyu Gan; Xiangyong Zheng; Min Zhao; Chunzhen Fan; Linna Du; Huanyi Miu (Process Safety and Environmental Protection, 2023)

PheLBD29, an LBD transcription factor from Moso bamboo, causes leaf curvature and enhances tolerance to drought stress in transgenic Arabidopsis - Min Wu; Wei He; Linna Wang; Xiaoyue Zhang; Kang Wang; Yan Xiang (Journal of Plant Physiology, 2023)

Comparative genomic analysis of the CPK gene family in Moso bamboo (Phyllostachys edulis) and the functions of PheCPK1 in drought stress - Min Wu; Hongxia Liu; Linna Wang; Xiaoyue Zhang; Wei He; Yan Xiang (Protoplasma, 2023)

Genome-wide analysis of CtNF-YB and lipid synthesis regulation of CtNF-YB12 in Carthamus tinctorius L. - Sinan Deng; Ruinan Wang; Chenlu Tao; Lixia Li; Shuai Wang; Chang Jia; Yilin Liu; Ruo Du; Linna Du; Jing Yang (Plant Cell Reports, 2023)

Sensitivity analysis of heat transfer coefficient in primary system for LMSR core power control system based on Sobol’s method - Lehua Liang; Chuhao Li; Linna Wang; Xuejian Wang; Wenjie Zeng; Run Luo (Annals of Nuclear Energy, 2023)

Remote Estimation of the Chlorophyll-a Concentration in Lake Dianshan, China Using High-Spatial-Resolution Satellite Imagery - Xiaoman Lu; Chunyan Situ; Jiajia Wang; Liguo Zhou; Weichun Ma; Linna Li (Journal of the Indian Society of Remote Sensing, 2022)

Identification and Expression Analysis of LBD Genes in Moso Bamboo (Phyllostachys edulis) - Yameng Gao; Kang Wang; Ruijia Wang; Linna Wang; Hongxia Liu; Min Wu; Yan Xiang (Journal of Plant Growth Regulation, 2022)

Heavy Precipitation over the Jing-Jin-Ji Region in Early October: What Controls Its Interannual Variability? - Jing Feng; Tim Li; Ji Wang; Linna Zhang (Journal of Meteorological Research, 2022)

Identification of TCP family in moso bamboo (Phyllostachys edulis) and salt tolerance analysis of PheTCP9 in transgenic Arabidopsis - Yuzeng Xu; Linna Wang; Hongxia Liu; Wei He; Nianqin Jiang; Min Wu; Yan Xiang (Planta, 2022)

Plant diversity has stronger linkage with soil fungal diversity than with bacterial diversity across grasslands of northern China - Congwen Wang; Linna Ma; Xiaoan Zuo; Xuehua Ye; Renzhong Wang; Zhenying Huang; Guofang Liu; Johannes H. C. Cornelissen (Global Ecology and Biogeography, 2022)
Aim The interactions between plants and soil microbes play crucial roles in modulating the function and stability of terrestrial ecosystems. However, the relationships between plant and soil microbial diversity for different taxa have remained been elusive. Location Northern China. Major taxa Plant and soil microbes of grassland ecosystems. Time period 2018 and 2019. Methods We conducted a transect survey across grasslands to measure plant diversity, plant traits, and soil microbial diversity. High throughput sequencing was used to assess soil microbial diversity for bacterial 16S ribosomal RNA (16S) and fungal internal transcribed spacer (ITS) regions on an Illumina MiSeq. The random forest algorithm was used to determine the important spatial and environmental variables in predicting plant and microbial diversity, and structural equation modelling was used to examine the direct and indirect effects of climatic and edaphic variables on plant and microbial diversity. Results Plant diversity was positively correlated with the diversity of soil fungi, particularly for predicted arbuscular mycorrhizal fungi (AMF) and saprotrophic fungi, and they were positively related to soil nutrients and texture. However, the correlation between plant and bacterial diversity varied by phyla and functional guilds, resulting in decoupling between plant and soil bacterial diversity. Community weighted mean leaf C:N ratio indirectly decreased soil fungal diversity through a negative relationship with soil total nitrogen. Soil bacterial and fungal diversity increased with increasing functional richness of specific leaf area and stem density, respectively. Main conclusions These findings have contributed to unravelling the direct and indirect linkages between plant and soil fungal diversity, highlighting particularly strong linkages between plant diversity and predicted AMF and saprotrophic fungi diversity. However, we failed to detect an overall linkage between plant and soil bacterial diversity. Still, our findings suggest that integrating soil fungi into the framework of plant diversity conservation is conducive to biodiversity restoration in degraded grassland ecosystems.

The poverty evolution of typical countries along the Belt and Road and implications from China’s poverty reduction experiences - Linna Shi; Yongsheng Wang; Yansui Liu; Yuheng Li (Journal of Geographical Sciences, 2022)

Component changes of mulberry leaf tea processed with honey and its application to in vitro and in vivo models of diabetes - Huixin Bai; Wei Jiang; Xufang Wang; Na Hu; Linna Liu; Xi Li; Yanhua Xie; Siwang Wang (Food Additives & Contaminants: Part A, 2021)

cFos-ANAB: A cFos-based Web Tool for Exploring Activated Neurons and Associated Behaviors - Fan Wang; Wenjie Sun; Lei Chang; Kefang Sun; Leying Hou; Linna Qian; Chaoyin Jin; Jiandong Chen; Jiali Pu; Panmeng Ye; Shuang Qiu; Jianhong Luo; et al. (Neuroscience Bulletin, 2021)

Knowledge mapping analysis of research progress and frontiers in integrated disaster risk management in a changing climate - Lihong Wang; Zaiwu Gong; Linna Shi; Zewen Hu; Ashfaq Ahmad Shah (Natural Hazards, 2021)

The complete mitochondrial genome of the hybrid grouper Epinephelus moara (♀)×Epinephelus tukula (♂), and phylogenetic analysis in subfamily Epinephelinae - Zhentong Li; Yongsheng Tian; Meiling Cheng; Linna Wang; Jingjing Zhang; Yuping Wu; Zunfang Pang; Wenhui Ma; Jieming Zhai (Acta Oceanologica Sinica, 2020)

De novo variants in the Helicase-C domain of CHD8 are associated with severe phenotypes including autism, language disability and overgrowth - Yu An; Linna Zhang; Wenwen Liu; Yunyun Jiang; Xue Chen; Xiaoping Lan; Gan Li; Qiang Hang; Jian Wang; James F. Gusella; Yasong Du; Yiping Shen (Human Genetics, 2020)

Investigation on the Effect of Capillary Microsampling on Hematologic and Toxicokinetic Evaluation in Regulatory Safety Studies in Mice - Bonnie Wang; Linna Wang; Alicja Batog; Thomas Brodie; Lila Ramaiah; Kristina D. Chadwick; Ting Su; Raja Mangipudy; Renuka C. Pilutla; Qin C. Ji (The AAPS Journal, 2020)

Precipitation data and their uncertainty as input for rainfall-induced shallow landslide models - Yueli Chen; Linna Zhao; Ying Wang; Qingu Jiang; Dan Qi (Frontiers of Earth Science, 2019)

Efficient isolation of protoplasts from freesia callus and its application in transient expression assays - Xiaotong Shan; Yueqing Li; Liudi Zhou; Linna Tong; Chao Wei; Lijun Qiu; Xiang Gao; Li Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Site-specific expression of IQGAP1 in human nephrons - Ping Wang; Xiaojie Gong; Peizhong Guan; Dong Ji; Linna Du; Dongmei Xu; Yipeng Liu (Journal of Molecular Histology, 2019)

Using magnetic susceptibility to evaluate pollution status of the sediment for a typical reservoir in northwestern China - Huiyun Pan; Xinwei Lu; Kai Lei; Dongqi Shi; Chunhui Ren; Linna Yang; Lijun Wang (Environmental Science and Pollution Research, 2019)

Research on Rare Cranes Population Response to Land Use Change of Nature Wetland - Wenjuan Peng; Bin Dong; Shuangshuang Zhang; Hui Huang; Xiaokang Ye; Linna Chen; Qiang Zhou; Jing Wu; Cheng Wang; Ming Zhu; Kangkang Zhao; Dian Lv (Journal of the Indian Society of Remote Sensing, 2018)

Circumjacent distribution pattern of the Lungmachian graptolitic black shale (early Silurian) on the Yichang Uplift and its peripheral region - Xu Chen; Qing Chen; Yongyi Zhen; Hongyan Wang; Linna Zhang; Junpeng Zhang; Wenhui Wang; Zhaohui Xiao (Science China Earth Sciences, 2018)

Cloning, Expression, and Biochemical Characterization of Two New Oligoalginate Lyases with Synergistic Degradation Capability - Shangyong Li; Linna Wang; Xuehong Chen; Wenwen Zhao; Mi Sun; Yantao Han (Marine Biotechnology, 2018)

Combining multi-source data to explore a mechanism for the effects of micrometeorological elements on nutrient variations in paddy land water - Hezhen Lou; Shengtian Yang; Changsen Zhao; Zhiwei Wang; Xiaolin Liu; Liuhua Shi; Linna Wu; Fanghua Hao; Mingyong Cai (Paddy and Water Environment, 2017)

A subclass of HSP70s regulate development and abiotic stress responses in Arabidopsis thaliana - Linna Leng; Qianqian Liang; Jianjun Jiang; Chi Zhang; Yuhan Hao; Xuelu Wang; Wei Su (Journal of Plant Research, 2017)

Accumulation and source of heavy metals in sediment of a reservoir near an industrial park of northwest China - Yuanjie Zhu; Xinwei Lu; Linna Yang; Lijun Wang (Frontiers of Earth Science, 2016)

Suitable hepatitis B vaccine for adult immunization in China - Linna Yang; Jun Yao; Jing Li; Yongdi Chen; Zheng-gang Jiang; Jing-jing Ren; Kai-jin Xu; Bing Ruan; Shi-gui Yang; Bing Wang; Tian-sheng Xie; Qian Li (Immunologic Research, 2016)

A new κ-carrageenase CgkS from marine bacterium Shewanella sp. Kz7 - Linna Wang; Shangyong Li; Shilong Zhang; Jiejing Li; Wengong Yu; Qianhong Gong (Journal of Ocean University of China, 2015)

Cloning, overexpression and characterization of a new oligoalginate lyase from a marine bacterium, Shewanella sp. - Linna Wang; Shangyong Li; Wengong Yu; Qianhong Gong (Biotechnology Letters, 2015)

Evaluating the suitability of TRMM satellite rainfall data for hydrological simulation using a distributed hydrological model in the Weihe River catchment in China - Haigen Zhao; Shengtian Yang; Zhiwei Wang; Xu Zhou; Ya Luo; Linna Wu (Journal of Geographical Sciences, 2015)

Purification and characterization of a new thermostable κ-carrageenase from the marine bacterium Pseudoalteromonas sp. QY203 - Shangyong Li; Panpan Jia; Linna Wang; Wengong Yu; Feng Han (Journal of Ocean University of China, 2013)

Estimating time-series leaf area index based on recurrent nonlinear autoregressive neural networks with exogenous inputs - Linna Chai; Yonghua Qu; Lixin Zhang; Shunlin Liang; Jindi Wang (International Journal of Remote Sensing, 2012)

Progresses on microwave remote sensing of land surface parameters - JianCheng Shi; Yang Du; JinYang Du; LingMei Jiang; LinNa Chai; KeBiao Mao; Peng Xu; WenJian Ni; Chuan Xiong; Qiang Liu; ChenZhou Liu; Peng Guo; et al. (Science China Earth Sciences, 2012)

NOTCH1 regulates migration and invasion of skin cancer cells by E-cadherin repression - Zhipeng Wang; Linna Liu; Meng Wang; Min Shen; Jing Li; Juanjuan Liu; Chen Li; Chunyan Xin; Shaojun Zhu; Qibing Mei; Yukun Wang (Molecular and Cellular Biochemistry, 2012)

Construction of an effective screening system for detection of Pseudomonas aeruginosa quorum sensing inhibitors and its application in bioautographic thin-layer chromatography - Linna Wang; Shanshan Zou; Shouliang Yin; Hongbing Liu; Wengong Yu; Qianhong Gong (Biotechnology Letters, 2011)

A rapid method for detection of PrP by surface plasmon resonance (SPR) - Wan Jiayu; Wang Xiong; Li Jiping; Liu Wensen; Xu Ming; Liu Linna; Xu Jing; Wang Haiying; Gao Hongwei (Archives of Virology, 2009)